2021
DOI: 10.1038/s41598-021-98239-7
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous demographics in post-bleach corals reveal boom-bust versus protracted declines

Abstract: Thermal-stress events have changed the structure, biodiversity, and functioning of coral reefs. But how these disturbances affect the dynamics of individual coral colonies remains unclear. By tracking the fate of 1069 individual Acropora and massive Porites coral colonies for up to 5 years, spanning three bleaching events, we reveal striking genus-level differences in their demographic response to bleaching (mortality, growth, and recruitment). Although Acropora colonies were locally extirpated, substantial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…These results indicate that S. stellata and M. cavernosa are afflicted by disease to different extents. Although these two species have massive growth form and may have similar susceptibility strategy (Loya et al 2001;Morais et al 2021), M. cavernosa is usually classified as a stress-tolerant species, while S. stellata is reported as weedy species (Darling et al 2012). Our finding agrees with this classification and supports previous studies that have shown the genus Siderastrea to have up to four times more prevalence of disease than the genus Montastraea (Calnan et al 2007).…”
Section: Resultssupporting
confidence: 90%
“…These results indicate that S. stellata and M. cavernosa are afflicted by disease to different extents. Although these two species have massive growth form and may have similar susceptibility strategy (Loya et al 2001;Morais et al 2021), M. cavernosa is usually classified as a stress-tolerant species, while S. stellata is reported as weedy species (Darling et al 2012). Our finding agrees with this classification and supports previous studies that have shown the genus Siderastrea to have up to four times more prevalence of disease than the genus Montastraea (Calnan et al 2007).…”
Section: Resultssupporting
confidence: 90%
“…Ultimately, mean seawater temperatures are perpetually rising around Pulau Lang Tengah (Figure 2), in addition to higher frequencies of thermal anomalies that surpass the thermal maxima of scleractinian taxa, causing repeated thermal stress. Regardless of differences in thermal tolerance and low mortality rates post bleaching events as those reported here (Figure 4 and Supplementary S5), such warming trends and resulting bleaching events selectively pressure scleractinian communities by altering scleractinian community assemblages (Loya et al, 2001; Baker et al, 2008, Hughes et al, 2018a), and likely influence demographic processes in surviving colonies who suffer high bleaching severity, such as massive Porites (Morais et al, 2021). Thus, severe annual coral bleaching will represent an imminent risk to coral reef survival and integrity (Van Hooidonk et al, 2017 (UNEP)).…”
Section: Discussionmentioning
confidence: 56%
“…We acknowledge that genetic and cellular process are underpinning heat stress response in hard corals and that these can only be investigated on species level (Grottoli et al, 2014;Schoepf et al, 2015;Guzman et al, 2018). However, there is strong evidence that certain functional traits required for establishing thermally tolerant populations after large scale disturbance events, are phylogenetically conserved on genus level (Darling et al, 2012;Morais et al, 2021). Such traits include growth, fecundity and reproductive mode, and further supporting evidence is presented by Alvarez-Noriega et al (2016), who suggest that fecundity can be predicted by coral colony morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations